Scale effect in Turkish manufacturing industry: Stochastic metafrontier analysis - Saeid Hajihassaniasl; Recep Kök (Journal of Economic Structures, 2016)
Economic theories explain the economic growth affected by accumulation of production factors and increase in productivity and efficiency. Traditional growth theories focus on the first factor where in developing countries, and especially due to the low input of capital, serious problems arise in the growth process. Accordingly, in these countries, increase in the productivity and efficiency and use of the excess capacity has focused. Therefore, the efficiency analysis of economic sectors of these countries, and especially the manufacturing sector and the factors that affect it, is very important to study. The main purpose of this study with respect to the indicators of efficiency of firms operating in Turkey manufacturing industry is to analyze the impact of scale differences on firm performance. The database used in this study is provided from the survey results (2006) belongs to Istanbul OSB, from the balance sheets and income statements of firms registered in IMKB, which operate in Turkey manufacturing industry for the 2006. Furthermore, the database for descriptive analyses was obtained from Statistics Department of Turkey (TUIK) and Turkey's Development Bank. As the analyzing method, the stochastic frontier is used as well as the metafrontier. According to the frontier function scores in the subsectors, in small-scale firms MP, FDT and MEMSAS subsectors and in medium- and large-scale firms OCP, FDT and TSL subsectors are the most efficient subsectors. Also, according to the metafrontier function scores in the subsectors, in small-scale firms MP, MMR and OCP subsectors and in medium- and large-scale firms MP, TSL and OCP subsectors are the most efficient subsectors. Some of the results of this study reveal that, except of food stuffs and drinks (FDT) oil, chemistry, petrochemical and its derivatives (OCP) subsectors, the production inefficiency which occurs in other subsectors due to conditions of increasing return to scale is significantly caused by the operation carried out below the optimal production scale. In addition, except BMI subsector, in all other subsectors, it is seen that production scale has large impact on the efficiency of the firm and also the average efficiency of medium- and large-scale firms in each subsector is higher than the average efficiency of small-scale firms of same subsector.
Keywords: C01; D24; L25; 330; Technical efficiency; Technology gap ratio; Stochastic frontier analysis; Turkey's manufacturing industry